Analysis of production and consumption foods in Lugansk region - Volvak, S.A. (Економічний вісник Донбасу, 2010)
The influence of production on the consumption of food in the Lugansk region on human health. The comparison of the experiences of developed countries, is justified, that in modern conditions the essential foundation for the success of agricultural enterprises is to regulate the state of parity prices for farm products and manufactured goods, financial support of the state and the restriction of entry of imported food products. Key words: food production and consumption, agricultural production, price parity, the support of the state.